Expression of Spiritual Connotation of Chinese Revolutionary Historical-Themed Oil Paintings in the 1970s - Li Hongxian; Azian Tahir; Syed Alwi Syed Abu Bakar; Li Jianan (Environment-Behaviour Proceedings Journal, 2025)
This study takes the revolutionary historical-themed oil paintings created in the 1970s in the collection of The Art of the Party as samples and studies the spiritual connotations contained in the revolutionary historical-themed oil paintings by analysing the content of textual documents and artworks and using relevant theory as the research instrument. The researcher aims to analyse textual data to uncover the historical background, conception process, and methods of expression in revolutionary historical-themed oil paintings. The ultimate goal is to contribute a new theoretical achievement to the study of these paintings.